Intraspecific variability drives functional changes in lichen epiphytic communities across Europe - Hurtado, Pilar; Prieto, María; Aragón, Gregorio; de Bello, Francesco; Martínez, Isabel (Ecology, 2020)
Traditional approaches in trait-based community ecology typically expect that trait filtering across broad environmental gradients is largely due to replacement of species, rather than intraspecific trait adjustments. Recently, the role of intraspecific trait variability has been largely highlighted as an important contributor mediating the ability of communities to persist under changing conditions and determining the community-level trait variation, particularly across limited environmental gradients. Unfortunately, few studies quantify the relative importance of species turnover versus intraspecific variability mediating the response of communities different from vascular plants. Here, we studied the functional changes in epiphytic lichen communities within 23 beech forests across large latitudinal (ca. 3,000 km) and environmental gradients in Europe to quantify the relative contribution of species turnover and intraspecific variability and the role of climate controlling community-level trait changes. For 58 lichen species, we focused on a set of 10 quantitative functional traits potentially affected by climatic conditions and related to photosynthetic performance (n = 1,184 thalli), water use strategy (n = 1,018 thalli), and nutrient uptake (n = 1,179 thalli). Our results showed that intraspecific trait variability explained most of the functional changes in lichen communities in response to the latitudinal gradient. Further, such functional changes were determined by the covariation between intraspecific trait variability and species turnover, which varied in sign depending on the trait considered. Finally, different climatic predictors explained functional variation due to both intraspecific trait variability and species turnover. We propose that lichen communities cope with contrasting climatic conditions by adjusting the functional trait values of the most abundant species within the communities rather than by the replacement of the species. Consequently, intraspecific variability should be explicitly incorporated to understand the effect of environmental changes on lichen communities, even over large environmental variations, better. Our results challenge the universality of the hypothesis that species turnover chiefly drives functional trait changes across large environmental gradients and call for a wider test of such important assumptions in trait ecology in different organism types and ecosystems.
Keywords: Lichens; Climate Change; ekosystém; Europe; community ecology; Evropa; lišejníky; functional ecology; klimatické změny; intraspecific variability; beech forests; lesy; species turnover; climate; lichen; latitudinal gradient; functional trait variation; Ecosystem; Forests